Implementasi Algoritma Sequential Search Dalam Game Edukasi Penyusunan Kalimat Terstruktur - Siddiq Alridho; Khairunnisa; Dharmawati (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
The problem in this research is that it is difficult to learn structured sentences, especially in composing words, due to minimal knowledge, so this research aims to implement the Sequential Search algorithm in an educational game which aims to help users in composing structured sentences. The Sequential Search algorithm is used to search for and arrange words sequentially according to correct grammatical rules. This game is designed to help players, especially children, understand the concept of constructing sentences correctly in language. This research uses data originating from Indonesian language books. Through the implementation of this algorithm, it is hoped that players can develop their skills in constructing sentences correctly and effectively, as well as improve their understanding of grammar. This research combines the concept of learning through games (game-based learning) with an understanding of the Sequential Search algorithm in the context of language education. It is hoped that the results of this research can make a positive contribution in improving players' abilities in the field of composing structured sentences.